HUBUNGAN HOMESICKNESS DENGAN TINGKAT KECEMASAN PADA MAHASISWA RANTAU DI KOTA SEMARANG - Amalia Dwi Rahmi; Shofwatun Amaliyah (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
The difficulties of sociocultural adaptation and geographic separation from primary family support systems during the transition to college are the background to this research. These operational issues trigger profound emotional distress, culture shock, and increased mental vulnerability among newcomers. The main focus of this scientific study is to analyze and empirically test the relationship between homesickness and anxiety levels among out-of-town students in Semarang City. The steps of this quantitative research pathway with a correlational design were operated through sampling using a non-probability sampling method. The primary data collection procedure involved 106 active respondents via an online questionnaire using the Utrecht Homesickness Scale and Generalized Anxiety Disorder-7 instruments. The quantitative data were statistically analyzed using a Pearson correlation test. The empirical results revealed a positive and significant relationship between the two variables with a correlation coefficient r of 0.545 and a significance value p of 0.000. These findings indicate that the higher the level of homesickness experienced by students, the greater the intensity of their psychological anxiety. The main conclusion confirms that homesickness acts as a crucial indicator factor in determining emotional stability. It is recommended that students from other countries and academic institutions draft adaptive coping strategies to reduce the accumulation of negative mental tension on an ongoing basis. ABSTRAK Kesulitan proses adaptasi sosiokultural serta keterpisahan geografis dari sistem dukungan utama keluarga pada masa transisi perkuliahan melatarbelakangi kegiatan penelitian ini. Masalah operasional tersebut memicu distres emosional mendalam, fenomena culture shock, dan peningkatan kerentanan mental pada kalangan pendatang baru. Fokus utama kajian ilmiah ini adalah membedah dan menguji secara empiris hubungan antara homesickness dengan tingkat kecemasan pada mahasiswa rantau di Kota Semarang. Langkah-langkah jalur riset kuantitatif dengan desain korelasional ini dioperasikan melalui penarikan sampel menggunakan metode non-probability sampling. Prosedur pengumpulan data primer melibatkan 106 responden aktif via kuesioner daring menggunakan instrumen Utrecht Homesickness Scale dan Generalized Anxiety Disorder-7. Data kuantitatif dianalisis statistik lewat uji korelasi Pearson. Hasil penelitian secara empiris menyingkap adanya hubungan positif dan signifikan antara kedua variabel dengan nilai koefisien korelasi r sebesar 0,545 serta nilai signifikansi p sebesar 0,000. Temuan ini menunjukkan bahwa semakin tinggi tingkat kerinduan rumah yang dialami mahasiswa, maka semakin meningkat pula intensitas kecemasan psikologisnya. Simpulan utama menegaskan bahwa homesickness bertindak sebagai salah satu faktor indikator krusial penentu stabilitas emosi. Mahasiswa perantau serta institusi akademik direkomendasikan menyusun draf strategi pengondisian koping adaptif guna mereduksi akumulasi ketegangan pikiran negatif secara berkelanjutan.